Emerging roles of cardiolipin remodeling in mitochondrial dysfunction associated with diabetes, obesity, and cardiovascular diseases - Shi, Yuguang (Editorial Department of Journal of Biomedical Research, 2010)
Cardiolipin (CL) is a phospholipid exclusively localized in inner mitochondrial membrane where it is required for oxidative phosphorylation, ATP synthesis, and mitochondrial bioenergetics. The biological functions of CL are thought to depend on its acyl chain composition which is dominated by linoleic acids in metabolically active tissues. This unique feature is not derived from the de novo biosynthesis of CL, rather from a remodeling process that involves in phospholipases and transacylase/acyltransferase. The remodeling process is also believed to be responsible for generation of CL species that causes oxidative stress and mitochondrial dysfunction. CL is highly sensitive to oxidative damages by reactive oxygen species (ROS) due to its high content in polyunsaturated fatty acids and location near the site of ROS production. Consequently, pathological remodeling of CL has been implicated in the etiology of mitochondrial dysfunction commonly associated with diabetes, obesity, heart failure, neurodegeneration, and aging that are characterized by oxidative stress, CL deficiency, and abnormal CL species. This review summarizes recent progresses in molecular, enzymatic, lipidomic, and metabolic studies that support a critical regulatory role of pathological CL remodeling as a missing link between oxidative stress and mitochondrial dysfunction in metabolic diseases and aging.